Effects of an electrostimulation training program on strength, jumping, and kicking capacities in soccer players - Billot, M.; Martin, A.; Paizis, C.; Cometti, C.; Babault, N. (The Journal of Strength and Conditioning Research, 2010)
The present study investigated the influence of a 5-week electrostimulation (EMS) training program on muscular strength, kicking velocity, sprint, and vertical jump performance in soccer players. Twenty amateur soccer players participated in the study, 10 in the electrostimulated group and the remaining 10 in a control group. Electrostimulation was applied on the quadriceps muscles over 5 weeks. Subjects were tested before, during (wk-3), and after (wk-5) the EMS training program. Maximal voluntary contraction using different contraction mode (i.e., eccentric, concentric, and isometric), vertical jump height, sprint running for 10 m, and ball speed were examined. We observed an increase in isometric and eccentric maximal knee extension torques and also a gain in ball speed performance without run up at wk-3. After 5 weeks of EMS training, eccentric, isometric, and concentric torques and ball speed had significantly improved. It appeared appropriate to conduct EMS training during at least 3 weeks to observe beneficial effects in specific soccer skills such as ball speed.